Force spectroscopy of chromatin fibers: extracting energetics and structural information from Monte Carlo simulations - Kepper, Frank Nikolaus; Ettig, Ramona; Stehr, Rene; Marnach, Sven; Wedemann, Gero; Rippe, Karsten (Biopolymers, 2011)
The folding of the nucleosome chain into a chromatin fiber is a central factor for controlling the DNA access of protein factors involved in transcription, DNA replication and repair. Force spectroscopy experiments with chromatin fibers are ideally suited to dissect the interactions that drive this process, and to probe the underlying fiber conformation. However, the interpretation of the experimental data is fraught with difficulties due to the complex interplay of the nucleosome geometry and the different energy terms involved. Here, we apply a Monte Carlo simulation approach to derive virtual chromatin fiber force spectroscopy curves. In the simulations, the effect of the nucleosome geometry, repeat length, nucleosome-nucleosome interaction potential, and the unwrapping of the DNA from the histone protein core on the shape of the force-extension curves was investigated. These simulations provide a framework for the evaluation of experimental data sets. We demonstrate how the relative contributions of DNA bending and twisting, nucleosome unstacking and unwrapping the nucleosomal DNA from the histone octamer can be dissected for a given fiber geometry.